Use of pressure muscle index to predict the contribution of patient’s inspiratory effort during pressure support ventilation: a prospective physiological study - Gao, Ran; Zhou, Jian-Xin; Yang, Yan-Lin; Xu, Shan-Shan; Zhou, Yi-Min; Zhang, Linlin; Miao, Ming-Yue (Frontiers in Medicine, 2024)
Background: The successful implementation of assisted ventilation depends on matching the patient's effort with the ventilator support. Pressure muscle index (PMI), an airway pressure based measurement, has been used as noninvasive monitoring to assess the patient's inspiratory effort. The authors aimed to evaluate the feasibility of pressure support adjustment according to the PMI target and the diagnostic performance of PMI to predict the contribution of the patient's effort during ventilator support.Methods: In this prospective physiological study, 22 adult patients undergoing pressure support ventilation were enrolled. After an end-inspiratory airway occlusion, airway pressure reached a plateau, and the magnitude of change in plateau from peak airway pressure was defined as PMI. Pressure support was adjusted to obtain the PMI which was closest to -1, 0, +1, +2, and +3 cmH2O. Each pressure support level was maintained for 20 minutes.Esophageal pressure was monitored. Pressure-time products of respiratory muscle and ventilator insufflation were measured, and the fraction of pressure generated by the patient was calculated to represent the contribution of the patient's inspiratory effort.Results: A total of 105 datasets were collected at different PMI-targeted pressure support levels. The differences in PMI between the target and the obtained value were all within ±1 cm H2O. As targeted PMI increased, pressure support settings decreased significantly from a median (interquartile range) of 11 (10-12) to 5 (4-6) cmH2O (P<0.001), which resulted in a significant increase in pressure-time products of respiratory muscle (from 2.9 [2.1-5.0] to 6.8 [5.3-8.1] cmH2O•s) and the fraction of pressure generated by the patient (from 25% [19%-31%] to 72% [62%-87%]) (P<0.001). The area under receiver operating characteristic curves for PMI to predict 30% and 70% contribution of patient's effort were 0.93 and 0.95, respectively. High sensitivity (all 1.00), specificity (0.86 and 0.78), and negative predictive value (all 1.00), but low positive predictive value (0.61 and 0.43) were obtained to predict either high or low contribution of patient's effort.Conclusions: Our results preliminarily suggested the feasibility of pressure support adjustment according to the PMI target from the ventilator screen. PMI could reliably predict the high and low contribution of a patient's effort during assisted ventilation.